Preparation method and application of MOF-derived heterostructure composite photocatalyst
By constructing a heterostructure composite photocatalyst of Fe2O3/Cu-Co3O4, the problem of slow degradation rate of MOF-based photocatalysts is solved, and efficient degradation of organic pollutants is achieved, with the advantages of low cost and easy operation.
Patent Information
- Application Number
- CN202411177061.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-26
AI Technical Summary
The catalytic degradation rate of MOF-based photocatalysts is slow and cannot meet the degradation needs of rapid treatment.
By mixing Cu-modified ZIF-67 (Co) with MIL-53 (Fe) and fully calcined, a heterostructure composite photocatalyst of Fe2O3/Cu-Co3O4 is constructed to improve the separation efficiency and oxidation of photogenerated electrons and holes. Reduction ability improves the activation rate of persulfate.
The catalytic degradation rate of photocatalysts on organic pollutants is significantly improved, and the efficient degradation effect is achieved, while also having the advantages of low cost and easy operation.
Smart Images

Figure CN119281327A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photocatalyst functional materials, and more specifically, relates to a preparation method and application of a MOF-derived heterostructure composite photocatalyst. Background Art
[0002] With the development of society and the progress of industry, water pollution is threatening human health. Dye wastewater has the characteristics of high concentration, high chroma, and high organic content. Among them, the organic pollutants in dye wastewater have potential hazards such as carcinogenicity, teratogenicity, and mutagenicity. The treatment effect of traditional biological treatment technology is poor, and the resulting economic losses and ecological damage are immeasurable. Therefore, removing organic pollutants from dye wastewater has become a major problem that scientific researchers urgently need to solve.
[0003] Photocatalytic technology has shown great potential in the fields of environmental governance and material transformation due to its unique light-induced oxidation ability, and has become a current research hotspot. Among them, metal organic framework (MOFs) materials have been widely used in the field of photocatalysis due to their unique pore structure and huge specific surface area, but their narrow light absorption range and limited catalytic active sites limit their photocatalytic degradation effect. Persulfate, as a class of strong oxidants, can be activated under light conditions to produce a variety of highly reactive strong oxidizing free radicals, which can quickly react with organic pollutants and degrade them into harmless small molecules. Studies have shown that the integration of persulfate into the MOFs-mediated photocatalytic system can greatly promote the activation efficiency of persulfate through the synergistic effect of the two, thereby achieving a significant improvement in photocatalytic degradation performance. For example, Vengatesan M. Rangaraj et al. (Rangaraj VM, Devaraju S, Reddy TG, et al. MOF-derived Co3O4@P-doped carbon nitride / α-Fe2O3 nanocomposite as a dual Z-scheme photocatalyst for persulfate mediated Bisphenol-A degradation [J]. Materials Research Bulletin, 2024, 179: 112925.) cleverly combined persulfate oxidation with MOFs photocatalytic technology to design a Co3O4@P-CN / α-Fe2O3 composite catalyst, which can degrade 99.3% of bisphenol A in 90 minutes. However, the degradation rate of the Co3O4@P-CN / α-Fe2O3 composite catalyst is still relatively slow and cannot meet the degradation requirements of rapid processing. Its catalytic rate needs to be further improved. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of MOF-based photocatalysts, that is, the catalytic degradation rate is still relatively slow and cannot meet the degradation requirements of rapid processing, and to provide a method for preparing a MOF-derived heterostructure composite photocatalyst.
[0005] Another object of the present invention is to provide a MOF-derived heterostructure composite photocatalyst prepared by the preparation method.
[0006] Another object of the present invention is to provide an application of a MOF-derived heterostructure composite photocatalyst in the degradation of organic pollutants.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] The present invention provides a method for preparing a MOF-derived heterostructure composite photocatalyst, comprising the following steps:
[0009] The Cu-modified ZIF-67 (Co) and MIL-53 (Fe) were mixed and fully calcined at 300-400 °C to obtain the MOF-derived heterostructure composite photocatalyst Fe2O3 / Cu-Co3O4;
[0010] The mass percentage of Cu in the Cu-modified ZIF-67(Co) is 7% to 9%.
[0011] The present invention introduces Cu to modify Co3O4 derived from ZIF-67(Co), and the introduction of Cu increases oxygen vacancies on its surface, thereby improving the separation efficiency of photogenerated electrons and holes. Then, Fe2O3 derived from MIL-53(Fe) is used as a carrier to load Cu-modified ZIF-67(Co) (i.e., ZIF-67(Cu-Co)) onto its surface, thereby combining two semiconductor materials with different band gap structures to construct a heterostructure. The introduction of Cu increases the number of oxygen vacancies on the surface of ZIF-67(Co), promotes the separation of photogenerated electrons and holes, and greatly improves the charge transfer efficiency; the synergistic effect generated by the heterostructure increases the specific surface area, improves the redox capacity, and improves the activation rate of persulfate, thereby improving the photocatalytic activity.
[0012] Furthermore, the mass proportion of Cu in the Cu-modified ZIF-67(Co) is 7% to 8%.
[0013] Furthermore, the mass ratio of the MIL-53 (Fe) to the ZIF-67 (Cu-Co) is 1: (1-2).
[0014] Preferably, the mass ratio of the MIL-53 (Fe) to the ZIF-67 (Cu-Co) is 1:1.
[0015] Furthermore, the heating rate of the calcination is 5 to 10° C. / min.
[0016] Furthermore, the calcination time is 4 to 6 hours.
[0017] Preferably, the mixing is carried out by grinding.
[0018] Furthermore, the preparation method of ZIF-67 (Cu-Co) comprises the following steps: fully mixing cobalt salt, copper salt, dimethylimidazole and water, and post-treating to obtain ZIF-67 (Cu-Co).
[0019] Furthermore, as a preferred manner, the preparation method of ZIF-67 (Cu-Co) includes the following steps: mixing cobalt salt, copper salt and water to obtain solution A; then mixing dimethylimidazole and water to obtain solution B, adding solution A to solution B, mixing thoroughly, and post-treating to obtain ZIF-67 (Cu-Co).
[0020] Furthermore, the preparation method of ZIF-67 (Cu-Co) may further include a surfactant, which can reduce the surface tension of the reaction system, thereby facilitating the reaction under milder conditions (such as lower temperature) and accelerating the reaction rate.
[0021] Furthermore, as a preferred method, the preparation method of ZIF-67 (Cu-Co) comprises the following steps: thoroughly mixing cobalt salt, copper salt, dimethylimidazole, surfactant and water, and post-treating to obtain ZIF-67 (Cu-Co).
[0022] Furthermore, the preparation method of ZIF-67 (Cu-Co) includes the following steps: mixing cobalt salt, copper salt, surfactant and water to obtain solution A; then mixing dimethylimidazole and water to obtain solution B, adding solution A to solution B, mixing thoroughly, and post-treating to obtain ZIF-67 (Cu-Co).
[0023] Furthermore, the surfactant includes one or more of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, and tetradecyltrimethylammonium bromide.
[0024] Furthermore, the cobalt salt includes cobalt nitrate, cobalt acetate, cobalt chloride or a hydrate of any of the above cobalt salts.
[0025] Furthermore, the copper salt is copper nitrate, copper acetate, copper sulfate or a hydrate of any of the above copper salts.
[0026] Furthermore, the molar ratio of cobalt in the cobalt salt, copper in the copper salt, dimethylimidazole and surfactant is 1: (0.04-0.25): (56-70): (0.005-0.03).
[0027] Furthermore, the molar ratio of cobalt in the cobalt salt, copper in the copper salt, dimethylimidazole, and surfactant is 1: (0.06-0.15): (58-65): (0.01-0.02).
[0028] Furthermore, the molar ratio of cobalt in the cobalt salt, copper in the copper salt, dimethylimidazole, and surfactant is 1:0.08:60:0.01. In actual calculations, due to different digits retained, the calculated results may be slightly different. For example, the calculated ratio is 1:0.081:60:0.0118, and the rounded result is 1:0.08:60:0.01 or 1:0.081:60:0.012, all of which belong to the protection scope of the present invention.
[0029] Furthermore, the mixing condition is stirring for 30 to 60 minutes.
[0030] Furthermore, the post-treatment includes centrifugation and drying.
[0031] Furthermore, the centrifugation is to centrifuge the mixed solution.
[0032] Furthermore, the drying is vacuum drying at 60-70° C. for 10-12 hours.
[0033] Specifically, the post-treatment is to centrifuge the mixed solution and then vacuum dry it at 60-70° C. for 10-12 hours.
[0034] Furthermore, the preparation method of MIL-53(Fe) comprises the following steps: mixing iron salt, terephthalic acid and polar organic solvent, reacting them sufficiently at 150-200° C., and post-treating them to obtain MIL-53(Fe).
[0035] Furthermore, the iron salt includes ferric chloride, ferroferric oxide, ferric oxide or a hydrate of any of the above iron salts.
[0036] Furthermore, the polar organic solvent includes one or more of N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide, preferably N,N-dimethylformamide.
[0037] Furthermore, the mixing ratio of iron in the iron salt, terephthalic acid, and polar organic solvent is 1 mmol: (0.25-4) mmol: (1.5-24) mL.
[0038] Furthermore, the mixing ratio of iron in the iron salt, terephthalic acid, and polar organic solvent is 1 mmol: (0.5-2) mmol: (2-10) mL.
[0039] Furthermore, the mixing ratio of iron in the iron salt, terephthalic acid, and polar organic solvent is 1 mmol:1 mmol:6 mL.
[0040] Furthermore, the post-treatment includes washing and drying.
[0041] Furthermore, the washing is to wash the product with ethanol and water for 3 to 5 times respectively.
[0042] Furthermore, the drying is vacuum drying at 60-70° C. for 10-12 hours.
[0043] Specifically, the post-treatment comprises washing the product with ethanol and water for 3 to 5 times respectively, and then vacuum drying at 60 to 70° C. for 10 to 12 hours.
[0044] The present invention protects the MOF-derived heterogeneous structure composite photocatalyst prepared by the above preparation method.
[0045] The present invention constructs a MOF-derived heterostructure composite photocatalyst by loading Cu-modified ZIF-67 (Co) on a Fe2O3 carrier derived from MIL-53 (Fe). The obtained composite photocatalyst has a larger specific surface area and more surface active sites, thus having better photocatalytic efficiency.
[0046] The invention protects the application of MOF-derived heterogeneous structure composite photocatalyst in degrading organic pollutants.
[0047] The principle of the MOF-derived heterostructure composite photocatalyst prepared by the present invention in degrading organic pollutants is as follows: the MOF-derived heterostructure composite photocatalyst prepared by the present invention is in full contact with the organic pollutants under light conditions (generally the light conditions are provided by a xenon lamp), and the interaction realizes a special catalytic and conversion effect, so that the surrounding oxygen and water molecules are excited into free radical anions with oxidizing ability to deactivate persulfate, thereby improving the photocatalytic efficiency, thereby achieving the purpose of efficiently degrading organic pollutants.
[0048] Persulfates mainly include peroxymonosulfate (PMS) and peroxydisulfate (PDS). In the photocatalytic degradation system, persulfate can be directly activated by the above-mentioned free radical anions to generate strong oxidizing species such as sulfate free radicals. Strong oxidizing free radicals can react with organic pollutants and be gradually oxidized and decomposed into harmless small molecules through various methods such as electron transfer, addition, and substitution, thereby achieving the degradation of organic pollutants.
[0049] Furthermore, the organic pollutants are organic pollutants containing a benzene ring structure.
[0050] Furthermore, the organic pollutants containing a benzene ring structure include one or more of rhodamine B, bisphenol A, methyl orange, methylene blue, and tetracycline.
[0051] Preferably, the organic pollutant containing a benzene ring structure is rhodamine B.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] The present invention introduces Cu to modify Co3O4 derived from ZIF-67 (Co), and then loads the modified Co3O4 on the surface of Fe2O3 derived from MIL-53 (Fe), and constructs a MOF-derived heterostructure composite photocatalyst by this method. The introduction of Cu increases the number of oxygen vacancies on the surface of ZIF-67 (Co), and improves the separation efficiency of photogenerated electrons and holes; the synergistic effect generated by the heterostructure increases the specific surface area, improves the redox ability, and increases the activation rate of persulfate, thereby increasing the catalytic degradation rate of organic pollutants by the obtained composite photocatalyst. In addition, the method does not cause waste of resources and secondary pollution, and has the advantages of low cost and easy operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 These are the X-ray diffraction patterns of Fe2O3 / Cu-Co3O4 prepared in Example 1, Fe2O3 prepared in Comparative Example 5, Co3O4 prepared in Comparative Example 6, Cu-Co3O4 prepared in Comparative Example 7, and Fe2O3 / Co3O4 prepared in Comparative Example 8.
[0055] Figure 2 This is a scanning electron microscope image of MIL-53(Fe) prepared in Example 1, with a magnification of 5,000 times.
[0056] Figure 3 This is a scanning electron microscope image of Fe2O3 derived from MIL-53(Fe) prepared in Comparative Example 5, with a magnification of 10,000 times.
[0057] Figure 4 This is a scanning electron microscope image of ZIF-67(Co) prepared in Example 1, with a magnification of 20,000 times.
[0058] Figure 5 This is a scanning electron microscope image of Co3O4 derived from ZIF-67(Co) prepared in Comparative Example 6, with a magnification of 20,000 times.
[0059] Figure 6This is a scanning electron microscope image of ZIF-67 (Cu-Co) prepared in Example 1, with a magnification of 15,000 times.
[0060] Figure 7 This is a scanning electron microscope image of Cu-Co3O4 derived from ZIF-67 (Cu-Co) prepared in Comparative Example 7, with a magnification of 15,000 times.
[0061] Figure 8 This is a scanning electron microscope image of Fe2O3 / Co3O4 prepared in Comparative Example 8, with a magnification of 10,000 times.
[0062] Fig. 9 This is a scanning electron microscope image of Fe2O3 / Cu-Co3O4 prepared in Example 1, with a magnification of 10,000 times.
[0063] Fig.10 This is the catalytic activity diagram of the photocatalytic activation of PMS for degradation of Rhodamine B by Fe2O3 / Cu-Co3O4-7.5 prepared in Example 1, Fe2O3 / Cu-Co3O4-5 prepared in Comparative Example 1, Fe2O3 / Cu-Co3O4-10 prepared in Comparative Example 2, Fe2O3 / Cu-Co3O4-15 prepared in Comparative Example 3, Fe2O3 / Cu-Co3O4-20 prepared in Comparative Example 4, Fe2O3 prepared in Comparative Example 5, Co3O4 prepared in Comparative Example 6, Cu-Co3O4-7.5 prepared in Comparative Example 7 and Fe2O3 / Co3O4 prepared in Comparative Example 8. DETAILED DESCRIPTION
[0064] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0065] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0066] Example 1 A MOF-derived heterostructure composite photocatalyst
[0067] 1. Experimental Methods
[0068] (1) Preparation of MIL-53(Fe)
[0069] Weigh ferric chloride hexahydrate (1.35 g) and terephthalic acid (0.83 g) and add them to N,N-dimethylformamide (30 mL) solution and stir for 30 minutes. Then transfer the uniform solution to a stainless steel autoclave lined with polytetrafluoroethylene and seal it. The reaction temperature is 150°C and the reaction time is 15 hours. The autoclave is cooled to room temperature. The obtained material is washed 3 times with ethanol and water, and then dried in vacuo at 60°C for 12 hours.
[0070] (2) Preparation of ZIF-67(Co)
[0071] Weigh cobalt nitrate hexahydrate (1.45 g) and hexadecyltrimethylammonium bromide (0.02 g), add them to a water (50 mL) solution and stir evenly to obtain solution A; weigh dimethylimidazole (22.7 g), add it to a water (350 mL) solution and stir for 30 min to obtain solution B; quickly pour solution A into solution B and stir for 30 min to obtain a purple precipitate, collect it by centrifugation, wash it 3 times with ethanol and water, and then dry it in vacuo at 60°C for 12 h.
[0072] (3) Preparation of ZIF-67(Cu-Co)
[0073] Weigh cobalt nitrate hexahydrate (1.35 g), copper nitrate (0.07 g) and hexadecyltrimethylammonium bromide (0.02 g), add them to a water (50 mL) solution and stir for 30 min to obtain a mixed solution C; then weigh dimethylimidazole (22.7 g) and add it to a water (350 mL) solution and stir for 30 min to obtain a solution D; quickly pour solution C into solution D and stir for 30 min, collect the resulting precipitate by centrifugation, wash 3 times with ethanol and water, and then dry it in vacuo at 60°C for 12 h.
[0074] (4) Preparation of Fe2O3 / Cu-Co3O4
[0075] Weigh the MIL-53(Fe) (0.1 g) obtained in step (1) and the ZIF-67(Cu-Co) (0.1 g) obtained in step (3) and grind them in an agate mortar. After grinding, pour the powder into a quartz crucible, and then put it into a muffle furnace. In an air atmosphere, calcine at 400° C. for 4 h at a heating rate of 5° C. / min, and finally cool to room temperature to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67(Cu-Co) is 7.5%. According to the mass proportion of Cu in ZIF-67(Cu-Co), the obtained product is named Fe2O3 / Cu-Co3O4-7.5.
[0076] 2. Experimental results
[0077] The product Fe2O3 / Cu-Co3O4-7.5 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was found that the degradation rate of Rhodamine B by the photocatalyst was 100% when the photocatalyst was irradiated with light for 10 minutes.
[0078] Example 2 A MOF-derived heterostructure composite photocatalyst
[0079] 1. Experimental Methods
[0080] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.35 g and 0.06 g, respectively, and the calcination temperature in step (4) was 300° C. to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 7%. The obtained product was named Fe2O3 / Cu-Co3O4-7 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0081] 2. Experimental results
[0082] The above-obtained product Fe2O3 / Cu-Co3O4-7 (10 mg) was weighed for photocatalytic degradation experiment. It was measured that the degradation rate of rhodamine B by the photocatalyst under illumination for 10 minutes was basically the same as that in Example 1.
[0083] Example 3 A MOF-derived heterostructure composite photocatalyst
[0084] 1. Experimental Methods
[0085] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.32 g and 0.08 g, respectively, and the calcination temperature in step (4) was 350° C. to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 9%. The obtained product was named Fe2O3 / Cu-Co3O4-9 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0086] 2. Experimental results
[0087] The above-obtained product Fe2O3 / Cu-Co3O4-9 (10 mg) was weighed for photocatalytic degradation experiment. It was measured that the degradation rate of rhodamine B by the photocatalyst under illumination for 10 minutes was basically the same as that in Example 1.
[0088] Comparative Example 1 A MOF-derived heterostructure composite photocatalyst
[0089] 1. Experimental Methods
[0090] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.38 g and 0.05 g, respectively, to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 5%. The obtained product was named Fe2O3 / Cu-Co3O4-5 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0091] 2. Experimental results
[0092] The above-obtained product Fe2O3 / Cu-Co3O4-5 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was found that the degradation rate of Rhodamine B by the photocatalyst was 82% when irradiated with light for 10 minutes.
[0093] Comparative Example 2 A MOF-derived heterostructure composite photocatalyst
[0094] 1. Experimental Methods
[0095] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.31 g and 0.09 g, respectively, to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 10%. The obtained product was named Fe2O3 / Cu-Co3O4-10 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0096] 2. Experimental results
[0097] The above-obtained product Fe2O3 / Cu-Co3O4-10 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was found that the degradation rate of Rhodamine B by the photocatalyst was 91% when irradiated with light for 10 minutes.
[0098] Comparative Example 3 A MOF-derived heterostructure composite photocatalyst
[0099] 1. Experimental Methods
[0100] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.24 g and 0.14 g, respectively, to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 15%. The obtained product was named Fe2O3 / Cu-Co3O4-15 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0101] 2. Experimental results
[0102] The above-obtained product Fe2O3 / Cu-Co3O4-15 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was measured that the degradation rate of Rhodamine B by the photocatalyst was 81% when irradiated with light for 10 minutes.
[0103] Comparative Example 4 A MOF-derived heterostructure composite photocatalyst
[0104] 1. Experimental Methods
[0105] The same steps as in Example 1 were carried out, except that the amounts of cobalt nitrate and copper nitrate added in step (3) were 1.16 g and 0.19 g, respectively, to obtain the product Fe2O3 / Cu-Co3O4. According to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67 (Cu-Co) was 20%, and the obtained product was named Fe2O3 / Cu-Co3O4-20 according to the mass proportion of Cu in ZIF-67 (Cu-Co).
[0106] 2. Experimental results
[0107] The above-obtained product Fe2O3 / Cu-Co3O4-20 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was found that the degradation rate of Rhodamine B by the photocatalyst was 79% when irradiated with light for 10 minutes.
[0108] Comparative Example 5 A MIL-53 (Fe) derived Fe2O3 photocatalyst
[0109] 1. Experimental Methods
[0110] (1) Preparation of MIL-53(Fe)
[0111] Weigh ferric chloride hexahydrate (1.35 g) and terephthalic acid (0.83 g) and add them to N,N-dimethylformamide (30 mL) solution and stir for 30 minutes. Then transfer the uniform solution to a stainless steel autoclave lined with polytetrafluoroethylene and seal it. The reaction temperature is 150°C and the reaction time is 15 hours. The autoclave is cooled to room temperature. The obtained material is washed 3 times with ethanol and water, and then dried in vacuo at 60°C for 12 hours.
[0112] (2) Preparation of Fe2O3 derived from MIL-53(Fe)
[0113] The above-obtained MIL-53(Fe) (0.1 g) was weighed and ground into an agate mortar. After grinding, the powder was poured into a quartz crucible, and then placed in a muffle furnace. It was calcined at 400°C for 4 h in an air atmosphere with a heating rate of 5°C / min. Finally, it was cooled to room temperature to obtain a Fe2O3 product derived from MIL-53(Fe).
[0114] 2. Experimental results
[0115] The product MIL-53(Fe)-derived Fe2O3 (10 mg) was weighed for photocatalytic degradation experiment, and the degradation rate of Rhodamine B by the photocatalyst was measured to be 68% when illuminated for 10 minutes.
[0116] Comparative Example 6 A ZIF-67(Co)-derived Co3O4 photocatalyst
[0117] 1. Experimental Methods
[0118] (1) Preparation of ZIF-67(Co)
[0119] Weigh cobalt nitrate hexahydrate (1.45 g) and hexadecyltrimethylammonium bromide (0.02 g), add them to a water (50 mL) solution and stir evenly to obtain solution A; weigh dimethylimidazole (22.7 g), add it to a water (350 mL) solution and stir for 30 min to obtain solution B; quickly pour solution A into solution B and stir for 30 min to obtain a purple precipitate, collect it by centrifugation, wash it 3 times with ethanol and water, and then dry it in vacuo at 60°C for 12 h.
[0120] (2) Preparation of Co3O4 derived from ZIF-67(Co)
[0121] The above-obtained ZIF-67(Co) (0.1 g) was weighed and ground into an agate mortar. After grinding, the powder was poured into a quartz crucible, and then placed in a muffle furnace. It was calcined at 400°C for 4 h in an air atmosphere with a heating rate of 5°C / min. Finally, it was cooled to room temperature to obtain a ZIF-67(Co)-derived Co3O4 product.
[0122] 2. Experimental results
[0123] The product ZIF-67(Co)-derived Co3O4 (10 mg) was weighed for photocatalytic degradation experiment, and the degradation efficiency of the photocatalyst for Rhodamine B was measured to be 71% when illuminated for 10 minutes.
[0124] Comparative Example 7 A ZIF-67 (Cu-Co) derived Cu-Co3O4 composite photocatalyst
[0125] 1. Experimental Methods
[0126] (1) Preparation of ZIF-67(Cu-Co)
[0127] Weigh cobalt nitrate hexahydrate (1.35 g), copper nitrate (0.07 g) and hexadecyltrimethylammonium bromide (0.02 g), add them to a water (50 mL) solution and stir for 30 min to obtain a mixed solution C; then weigh dimethylimidazole (22.7 g) and add it to a water (350 mL) solution and stir for 30 min to obtain a solution D; quickly pour solution C into solution D and stir for 30 min, collect the resulting precipitate by centrifugation, wash 3 times with ethanol and water, and then dry it in vacuo at 60°C for 12 h.
[0128] (2) Preparation of Cu-Co3O4 derived from ZIF-67 (Cu-Co)
[0129] The above-obtained ZIF-67(Cu-Co) (0.1 g) was weighed and ground in an agate mortar. After grinding, the powder was poured into a quartz crucible, and then placed in a muffle furnace. It was calcined at 400°C for 4 hours in an air atmosphere with a heating rate of 5°C / min, and finally cooled to room temperature to obtain a Cu-Co3O4 product derived from ZIF-67(Cu-Co). Among them, according to ICP elemental analysis, the mass proportion of Cu in the obtained ZIF-67(Cu-Co) was 7.5%. According to the mass proportion of Cu in ZIF-67(Cu-Co), the obtained product was named Cu-Co3O4-7.5.
[0130] 2. Experimental results
[0131] The product ZIF-67 (Cu-Co)-derived Cu-Co3O4-7.5 (10 mg) was weighed for photocatalytic degradation experiment, and it was measured that the degradation efficiency of the photocatalyst for Rhodamine B was 93% when illuminated for 10 minutes.
[0132] Comparative Example 8 A MOF-derived Fe2O3 / Co3O4 heterostructure composite photocatalyst
[0133] 1. Experimental Methods
[0134] (1) Preparation of MIL-53(Fe)
[0135] Weigh ferric chloride hexahydrate (1.35 g) and terephthalic acid (0.83 g) and add them to N,N-dimethylformamide (30 mL) solution and stir for 30 minutes. Then transfer the uniform solution to a stainless steel autoclave lined with polytetrafluoroethylene and seal it. The reaction temperature is 150°C and the reaction time is 15 hours. The autoclave is cooled to room temperature. The obtained material is washed 3 times with ethanol and water, and then dried in vacuo at 60°C for 12 hours.
[0136] (2) Preparation of ZIF-67(Co)
[0137] Weigh cobalt nitrate hexahydrate (1.45 g) and hexadecyltrimethylammonium bromide (0.02 g), add them to a water (50 mL) solution and stir evenly to obtain solution A; weigh dimethylimidazole (22.7 g), add it to a water (350 mL) solution and stir for 30 min to obtain solution B; quickly pour solution A into solution B and stir for 30 min to obtain a purple precipitate, collect it by centrifugation, wash it 3 times with ethanol and water, and then dry it in vacuo at 60°C for 12 h.
[0138] (3) Preparation of Fe2O3 / Co3O4
[0139] Weigh the MIL-53(Fe) (0.1 g) obtained in step (1) and the ZIF-67(Co) (0.1 g) obtained in step (2) and grind them in an agate mortar. After grinding, pour the powder into a quartz crucible, and then put it into a muffle furnace. In an air atmosphere, calcine at 400°C for 4 h with a heating rate of 5°C / min. Finally, cool to room temperature to obtain the product Fe2O3 / Co3O4.
[0140] 2. Experimental results
[0141] The product Fe2O3 / Co3O4 (10 mg) was weighed and subjected to a photocatalytic degradation experiment. It was found that the degradation efficiency of the photocatalyst for Rhodamine B was 78% when the photocatalyst was irradiated with light for 10 minutes.
[0142] Experimental Examples Determination of the Physical and Chemical Properties of the Photocatalysts Described in Example 1 and Comparative Examples 1 to 8
[0143] 1.XRD test
[0144] from Figure 1It can be seen that the characteristic peaks of Fe2O3 of Comparative Example 5 and Co3O4 of Comparative Example 6 were detected in the characteristic peaks of Fe2O3 / Co3O4 obtained after calcination of Comparative Example 8, indicating that the two materials were successfully composited; after the introduction of Cu, the characteristic peak positions of Cu-Co3O4 and Fe2O3 / Cu-Co3O4 obtained in Example 1 were basically the same as the characteristic peak positions of Co3O4 of Comparative Example 6 and Fe2O3 / Co3O4 of Comparative Example 8, indicating that the introduction of Cu will not destroy the original crystal structure.
[0145] 2. SEM test
[0146] from Figure 2 It can be seen that the MIL-53(Fe) prepared in Example 1 has a regular hexagonal bipyramid structure and a smooth surface.
[0147] from Figure 3 It can be seen that the Fe2O3 derived from MIL-53(Fe) prepared in Comparative Example 5 still maintains the original crystal structure of MIL-53(Fe), and a large number of pore structures appear on the surface.
[0148] from Figure 4 It can be seen that the ZIF-67(Co) prepared in Example 1 has a regular dodecahedral structure and a relatively smooth surface.
[0149] from Figure 5 It can be seen that the ZIF-67(Co)-derived Co3O4 prepared in Comparative Example 6 still maintains the original ZIF-67(Co) crystal structure, but due to the collapse of the metal skeleton after calcination, the surface of Co3O4 becomes rough and many pores appear, which is beneficial to improve the absorption rate of visible light, thereby improving the photocatalytic performance.
[0150] from Figure 6 It can be seen that after the introduction of Cu, the ZIF-67(Cu-Co) prepared in Example 1 still maintains the same regular dodecahedral structure as ZIF-67(Co), and the surface is relatively smooth. This shows that the introduction of Cu does not destroy the original crystal structure, which is consistent with Figure 1 The results of XRD are consistent with those of
[0151] from Figure 7 It can be seen that the Cu-Co3O4 derived from ZIF-67 (Cu-Co) prepared in Comparative Example 7 basically maintains the same crystal structure as ZIF-67 (Cu-Co), but due to the collapse of the metal skeleton after calcination, the surface of Cu-Co3O4 becomes rough and many pores appear, which is beneficial to improve the absorption rate of visible light, thereby improving the photocatalytic performance.
[0152] from Figure 8It can be seen that the MOF-derived Fe2O3 / Co3O4 prepared in Comparative Example 8 maintains the original crystal structures of Fe2O3 and Co3O4, respectively, and Co3O4 is attached to the outer surface of Fe2O3.
[0153] from Fig. 9 It can be seen that after the introduction of Cu, the Fe2O3 / Cu-Co3O4 prepared in Example 1 still maintains the original crystal structure of Fe2O3 / Co3O4, indicating that the introduction of Cu does not destroy the original crystal structure. The crystal structure of Fe2O3 / Cu-Co3O4 obtained in Examples 2 to 3 and Comparative Examples 1 to 4 is consistent with that in Example 1, and will not be repeated here.
[0154] 3. Determination of the catalytic degradation efficiency of the photocatalysts obtained in Example 1 and Comparative Examples 1 to 8
[0155] (1) Determination of adsorption activity
[0156] The experiment was carried out in a DW-01 photochemical reactor, but without turning on the light source. 100 mL of Rhodamine B (concentration of 50 mg / L) simulated dye wastewater was added to the reactor and its initial value was determined. Then 0.1 g of photocatalyst was added, the light was not turned on, magnetic stirring was performed for 30 minutes, sampling was performed for analysis, and the supernatant was taken after centrifugal separation to determine its concentration at λ=554 nm using an ultraviolet spectrophotometer. The degradation rate Dr was calculated using the formula: Q=(C0-C)V / m, where C0 is the initial concentration of the Rhodamine B solution, C is the concentration of the Rhodamine B solution when it reaches adsorption equilibrium, V is the volume of the solution, and m is the mass of the added catalyst.
[0157] from Fig.10 It can be seen that all samples were Fig.10 From 30 minutes before the start of the experiment to 0 minutes before the start of illumination, that is, the -30 to 0 minute stage), the concentration C of the Rhodamine B solution when it reaches adsorption equilibrium is basically the same as the initial concentration C0 of the Rhodamine B solution (C / C0≈1). After confirming that such an equilibrium state has been reached, the subsequent illumination experiment can ensure that the reduction in the concentration of Rhodamine B is entirely attributed to the photocatalytic effect. This experimental design ensures the accuracy and repeatability of the experiment, and at the same time shows that the active sites on the catalyst surface have fully adsorbed enough reactant molecules, which is conducive to the smooth progress of the photocatalytic reaction.
[0158] (2) Degradation efficiency determination
[0159] In a DW-01 photochemical reactor, 100 mL of Rhodamine B (concentration of 50 mg / L) simulated dye wastewater was added to the reactor and its initial value was determined, then the prepared photocatalyst was added, magnetic stirring was performed for 30 minutes, sampling and analysis were performed, and the supernatant was taken after centrifugation to determine its concentration at λ=554 nm in an ultraviolet spectrophotometer, the sample was poured back into the reactor, and 10 mg of PMS was added, and then irradiated with a xenon lamp, and sampling and analysis were performed at intervals of 2 minutes during the illumination process, and the supernatant was taken after centrifugation to determine the absorbance at λ=554 nm in an ultraviolet spectrophotometer, and the degradation rate Dr was calculated by the formula: Dr=(C0-C)×100 / C0, where C0 is the initial concentration of the Rhodamine B solution 0, C is the concentration of the Rhodamine B solution measured at time t, and t is the reaction time. The wavelength and power of the xenon lamp are 420 nm and 50 W, respectively.
[0160] from Fig.10 It can be seen that the Fe2O3 / Cu-Co3O4 obtained by the present invention has a good degradation effect. Among them, the mass proportion of Cu in ZIF-67 (Cu-Co) will significantly affect its photodegradation efficiency. As the mass proportion of Cu in ZIF-67 (Cu-Co) increases, the degradation rate of Fe2O3 / Cu-Co3O4 catalyst activated PMS to degrade Rhodamine B shows a trend of first increasing and then decreasing. When the mass proportion of Cu added in ZIF-67 (Cu-Co) is 7.5%, the corresponding (Example 1) Fe2O3 / Cu-Co3O4-7.5 catalyst activated PMS to degrade Rhodamine B has the highest degradation efficiency, and the degradation rate reaches 100% within 10 minutes of illumination. In addition, when the amount of Cu added in ZIF-67 (Cu-Co) accounts for 7% and 9% by mass respectively, the corresponding Fe2O3 / Cu-Co3O4-7 and Fe2O3 / Cu-Co3O4-9 have catalytic effects close to those of Fe2O3 / Cu-Co3O4-7.5, and are overall better than the catalytic effect of Cu-Co3O4-7.5, which will not be repeated here.
[0161] The photodegradation efficiencies of Fe2O3 / Cu-Co3O4-5, Fe2O3 / Cu-Co3O4-10, Fe2O3 / Cu-Co3O4-15, Fe2O3 / Cu-Co3O4-20 with other Cu mass proportions in the comparative example, as well as MIL-53(Fe)-derived Fe2O3, ZIF-67(Co)-derived Co3O4, ZIF-67(Cu-Co)-derived Cu-Co3O4-7.5 and MOF-derived Fe2O3 / Co3O4 in 10 min were 82%, 91%, 81%, 79%, 68%, 71%, 93% and 78%, respectively, and the catalytic effects were all worse than those of Fe2O3 / Cu-Co3O4 obtained in the example.
[0162] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a MOF-derived heterostructure composite photocatalyst, characterized in that: The following steps are involved: The Cu-modified ZIF-67 (Co) and MIL-53 (Fe) were mixed and fully calcined at 300-400 °C to obtain the MOF-derived heterostructure composite photocatalyst Fe2O3 / Cu-Co3O4; The mass percentage of Cu in the Cu-modified ZIF-67(Co) is 7% to 9%.
2. The preparation method according to claim 1, characterized in that: The preparation method of the Cu-modified ZIF-67(Co) comprises the following steps: fully mixing cobalt salt, copper salt, dimethylimidazole and water, and post-treating to obtain the Cu-modified ZIF-67(Co).
3. The preparation method according to claim 1, characterized in that: The preparation method of MIL-53 (Fe) comprises the following steps: mixing iron salt, terephthalic acid and polar organic solvent, fully reacting at 150-200° C., and post-treating to obtain MIL-53 (Fe).
4. The preparation method according to claim 1, characterized in that: The mass proportion of Cu in the Cu-modified ZIF-67(Co) is 7% to 8%.
5. The preparation method according to claim 2, characterized in that: The cobalt salt includes cobalt nitrate, cobalt acetate, cobalt chloride or a hydrate of any of the above cobalt salts.
6. The preparation method according to claim 2, characterized in that: The copper salt includes copper nitrate, copper acetate, copper sulfate or a hydrate of any of the above copper salts.
7. A MOF-derived heterostructure composite photocatalyst prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the MOF-derived heterostructure composite photocatalyst according to claim 7 in the degradation of organic pollutants.
9. The use according to claim 8, characterized in that: The organic pollutants are organic pollutants containing benzene rings.
10. The use according to claim 9, characterized in that: The organic pollutants containing benzene rings include one or more of rhodamine B, bisphenol A, methyl orange, methylene blue, and tetracycline.
Citation Information
Patent Citations
Preparation and application of copper-cobalt / carbon catalyst derived from metal organic framework material
CN113713816A
Cobalt-copper binary metal oxide catalyst for catalytic combustion of VOCs gas and preparation method of cobalt-copper binary metal oxide catalyst
CN117718047A
Preparation method and application of atom encapsulated MOFs (Metal-Organic Frameworks) derived nano polyhedral catalyst
CN118320849A
Sunlight active composite photocatalyst for water purification
US20160207030A1